Conventional and complementary cancer treatments: where do conventional and complementary providers seek information about these modalities? - Trine Stub; Sara A. Quandt; Thomas A. Arcury; Joanne C. Sandberg; Agnete E. Kristoffersen (BMC, 2018)
Abstract Background Both conventional health care providers and complementary therapists treat cancer patients. To provide effective treatment, both types of providers should to be familiar with their own as well as alternative types of treatment. Our aim was to compare how conventional health care providers (oncology doctors, oncology nurses, family physicians) and complementary therapists (acupuncturists, reflexologists, massage therapists) seek information about conventional and complementary cancer treatments. Method This analysis was conducted on the basis of feedback from 466 participants. We used self-administered questionnaires in a cross-sectional study. Results The majority of the medical doctors (96%) searched for evidence-based information regarding conventional cancer treatments. They gathered this information mostly from guidelines, which is considered best practice and is expected from Norwegian health personnel. Eighty-one percent of the nurses gather this information from evidence based resources such as UpToDate. Colleagues were asked for information by 58% of the medical doctors and 64% of the nurses. Moreover, 50% of the medical doctors and 57% of the nurses searched for evidence-based information about complementary cancer modalities. The acupuncturists gathered evidence-based information for both conventional (79%) and complementary (77%) modalities, followed by the reflexologists (54 and 54%, respectively) and massage therapists (54 and 52%, respectively). Nearly half of the acupuncturist (49%) asked a colleague for information. Conclusion To provide safe cancer care, it is important that advice about complementary modalities is based on current and evidence-based evaluations. The majority of the medical doctors and nurses in this study sought information according to evidence-based medicine regarding conventional cancer treatments, and about half of them gathered evidence-based information about complementary cancer modalities. This was also true for the complementary therapists as they gathered information about complementary and conventional treatments from evidence-based evaluations. This demonstrates that since the term evidence-based medicine was first introduced in 1991, the approach has grown extensively and both conventional and complementary providers use this approach to seek information.